Development of a traditional Chinese medicine‐based agent for the treatment of cancer cachexia. Issue 4 (19th June 2022) - Wu, Kun‐Chang; Chu, Po‐Chen; Cheng, Yu‐Jung; Li, Chia‐Ing; Tian, Jingkui; Wu, Hsing‐Yu; Wu, Szu‐Hsien; Lai, Yi‐Chun; Kao, Hsiang‐Han; Hsu, Ao‐Lin; Lin, Hsiang‐Wen; Lin, Chih‐Hsueh
Abstract: Background: Despite recent advances in understanding the pathophysiology of cancer cachexia, prevention/treatment of this debilitating disease remains an unmet medical need. Methods: We developed an integrated, multi‐tiered strategy involving both in vitro and in vivo muscle atrophy platforms to identify traditional Chinese medicine (TCM)‐based anti‐cachectic agents. In the initial screening, we used inflammatory cytokine‐induced atrophy of C2C12 myotubes as a phenotypic screening platform to assess the protective effects of TCMs. The selected TCMs were then evaluated for their abilities to protect Caenorhabditis elegans from age‐related reduction of mobility and contractility, followed by the C‐26 colon adenocarcinoma mouse model of cachexia to confirm the anti‐muscle atrophy effects (body/skeletal muscle weights, fibre size distribution, grip strengths, and serum IL‐6). Transcriptome analysis, quantitative real‐time polymerase chain reaction, and immunoblotting were performed to gain understanding of the potential mechanism(s) by which effective TCM protected against C26 tumour‐induced muscle atrophy. Results: Of 29 widely used TCMs, Dioscorea radix (DR) and Mu Dan Pi (MDP) showed a complete protection (all P values, 0.0002) vis‐à‐vis C26 conditioned medium control in the myotube atrophy platform. MDP exhibited a unique ability to ameliorate age‐associated decreases in worm mobility, accompanied by improved total body contractions, relative to control ( P  < 0.0001 and <0.01, respectively), which, however, was not noted with DR. This differential in vivo protective effect between MDP and DR was also confirmed in the C‐26 mouse model. MDP at 1000 mg/kg (MDP‐H) was effective in protecting body weight loss ( P  < 0.05) in C‐26 tumour‐bearing mice without changing food or water intake, accompanied by the restoration of the fibre size distribution of hindleg skeletal muscles ( P  < 0.0001) and the forelimb grip strength ( P  < 0.05). MDP‐treated C‐26‐tumour‐bearing mice were alert, showed normal posture and better body conditions, and exhibited lower serum IL‐6 levels ( P  = 0.06) relative to vehicle control. This decreased serum IL‐6 was associated with the in vitro suppressive effect of MDP (25 and 50 μg/mL) on IL‐6 secretion into culture medium by C26 cells. RNA‐seq analysis, followed by quantitative real‐time polymerase chain reaction and/or immunoblotting, shows that MDP's anti‐cachectic effect was attributable to its ability to reverse the C‐26 tumour‐induced re‐programming of muscle homoeostasis‐associated gene expression, including that of two cachexia drivers (MuRF1 and Atrogin‐1), in skeletal muscles. Conclusions: All these findings suggest the translational potential of MDP to foster new strategies for the prevention and/or treatment of cachexia. The protective effect of MDP on other types of muscle atrophy such as sarcopenia might warrant investigations.